English literature from the 19th century through today - Luebering, J. E.; Gale Group (New York Britannica Educational Pub. in association with Rosen Educational Services, 2011)
This book describes the literary development in English literature from the 19th Century through today.
ch 1. The post-romantic and Victorian eras -- ch 2. The 20th century : from 1900 to 1945 -- ch 3. Literature after 1945.
Electronic reproduction.
Keywords: English literature -- 19th century -- History and criticism; English literature -- 20th century -- History and criticism